(untitled) (European Journal of Interdisciplinary Research and Development, 2024)
Industrial fires are the most costly compared to other fires. Water is the most common fire extinguishing agent because it has a set of physical and chemical properties that make it a very effective means of extinguishing, as it is applied either manually or automatically. The theoretical amounts of water needed for actual extinguishing are very low when calculated and provided in an effective manner. Therefore, it was necessary to propose several numerical models to estimate the amount of water that must be available in these buildings to extinguish fires if they occur or until support arrives from fire departments to complete the extinguishing process with the least possible loss of life and property that occurs in burning industrial buildings and nearby buildings that are exposed to fire. This research seeks to determine the relationship between firefighting water requirements and building design by reviewing current methods found in the literature for calculating firefighting water requirements and flow rates and discussing the extent to which they can be applied in the context of fire service procedures in industrial buildings. These flow rates can then be compared to the total capacity available at these buildings to determine if the available resources are sufficient. Some of these methods are designed to be interactive, so that the user can immediately see the effects of different parameters on the desired water flow rate. The ISO method and the Fire Risk Management Program method of the National Research Center of Canada are the most detailed and effective methods in taking into account many different factors, specifically related to the structure of the building and its relationship to neighboring buildings. Given that many fire service tasks depend on location, the importance of utilizing Geographic Information Systems to support fire service institutions has emerged, and by storing spatial data and making effective use of it, dynamic fire maps can produced and utilized in analyzing industrial building fires and predicting the effective ways to suppress them.